Identifying the Conditions Required for the NaOH Method for Producing Pulp and Paper from Sorghum Grown In Turkey - Gençer, Ayhan; Sahin, Memduh; Gençer, Ayhan (North Carolina State Univ Dept Wood & Paper Sci, 2015)
This study examines the possibilities of making pulp from sorghum grown in Bartin via the NaOH method. While setting the cooking conditions for producing pulp from annual plants, NaOH was used in quantities that amounted to 14, 16, 18, and 20% of the total weight of the dry sample. Optimum conditions were established relative to pulp yield, Kappa number, and a scoring table based on mechanical, optical, and physical values. Accordingly, optimum conditions for pulp production from sorghum stalks occurred when 20% NaOH was used at 120 degrees C, a 5:1 solution-to-stalk ratio, and a cooking time of 60 min.
Keywords: Sorghum Bicolor Sudanense; Pulp And Paper; Naoh Method